Periurethral and vulval condylomata acuminata: an unusual juvenile venereal disease in a 3-year-old girl. (8th September 2014) - Patel, Ramnik V; Desai, Divyesh; Cherian, Abraham; Martyn-Simmons, Claire
Abstract : We present a case of giant condyloma acuminatum (CA) in a 3-year-old girl with rapidly growing vulval and periurethral lesions, which was investigated thoroughly and successfully treated with excision biopsy. Genital warts in the form of giant alarming vestibular, vulval and periurethral lesions of CA are very rare in children. There is need for a multidisciplinary approach with potential sociomedicolegal implications. Surgical excision is safe, effective and provides an opportunity to assess the extent of the lesion and tissue for accurate diagnosis. Genital warts in the form of giant alarming vestibular, vulval and periurethral lesions of CA are very rare in children. Indications for surgical treatment include large, recurrent or refractory lesions, as well as the need for histological identification and acquiring tissue for immunotherapy when necessary. The strategy of an extended follow-up is recommended so as to ensure identification of any risk situations.